Dual function miR-205 is positively associated with ER and negatively with five-year survival in breast cancer patients - Petrović, Nina; Todorović, Lidija; Nedeljković, Milica; Božović, Ana; Bukumirić, Zoran; Tanić, Nasta Dedović; Jovanović-Ćupić, Snežana; Šami, Ahmad; Mandušić, Vesna (Pathology, research and practice, 2022)
Background - Precise molecular characterization of breast cancer, especially triple negative (TNBC) as the most lethal subtype, is needed to stratify patients for the individual treatment approach. MicroRNA-205 (miR-205) has tumor-suppressive and oncogenic functions across different cancers. Therefore, miR-205 might have a different role in TNBC and estrogen receptor (ER) positive BC. Our aim was to investigate how miR-205 expression is associated with ER/progesteron receptor status, clinical parameters, pathohistological characteristics of BC, and survival of patients - Methods - We determined miR-205 relative expressions in 73 primary breast tumors (50 TNBC and 23 ER+) by quantitative Real-time polymerase chain reaction (qPCR) and compared it to clinicopathological characteristics and outcome. - Results - The highest levels of miR-205 were in the ER+ /PR+ group, and the lowest in the TNBC group (p = 0.009). Significantly higher levels of miR-205 were also observed in the ER+ compared with the ER-negative group, regardless of the PR status (p = 0.002). Low miR-205 expression level was associated with prognostic stage III in TNBC samples (p = 0.049). Patients who received adjuvant chemotherapy had significantly lower levels of miR-205 (p = 0.016). Patients who received hormone therapy had significantly higher levels of miR-205 (p = 0.007). The low-miR-205 patients had significantly higher 5-year survival rates (p = 0.041). - Conclusion - The expression of miR-205 in BC is subtype-specific and high expression is associated with the ER+ tumors. The miR-205 expression might be a useful marker of TNBC progression. High miR-205 expression had a detrimental effect on BC patient outcome. Our results indicate that miR-205 might be utilized in clinical practice as a biomarker and an adjunct parameter for the selection of the most effective therapeutic modality.